Cystoisospora suis Control in Europe Is Not Always Effective - Hinney, Barbara; Cvjetković, Vojislav; Espigares, David; Vanhara, Jonas; Waehner, Christoph; Ruttkowski, Bärbel; Selista, Radinka; Sperling, Daniel; Joachim, Anja (Frontiers in Veterinary Science, 2020)
After the introduction of the anticoccidial toltrazuril for the metaphylactic treatment of suckling piglet coccidiosis, only few field evaluations on the effect of treatment against the causative agent, Cystoisospora suis, were performed. In 2018, a field study was conducted to detect the presence of the parasite on pig farms in four different European countries, and to evaluate management parameters possibly associated with infection and disease. A total of 49 farms from Austria, the Czech Republic, Germany and Spain were included. Repeated pooled faecal samples from 603 litters were taken in the 2nd and 3rd week of life. Samples were examined by autofluorescence for the presence of C. suis, and faecal consistency was scored. For each farm a questionnaire was provided to document management and treatment history. Faeces scored as diarrhoeic were not significantly more often positive for C. suis than non-diarrhoeic faeces but samples from litters with previously reported occurrence of diarrhoea were significantly more often positive (p = 0.003). Pasty faeces were significantly more often positive than those of other consistency (p = 0.000). Overall, 71.4% of the farms and 50.1% of the litters were positive for C. suis at least once. The prevalence on the farms reached up to 100%. Diarrhoea was seen in samples from 53.1% of the farms (9.6% of the litters). C. suis was diagnosed on 80.8% of the farms with vs. 60.8% of those without diarrhoea. Toltrazuril was applied on 30 farms, and of these 53.3% had diarrhoeic samples and 66.7% were positive for C. suis versus 19 farms that did not use toltrazuril with 52.6% diarrhoeic and 79.0% C. suis positive samples (p > 0.05). Only on two farms a disinfectant with activity against coccidia was used, and C. suis was not detected there. Current control of C. suis appears to be insufficient on the majority of the examined farms. These findings highlight the importance of the correct application of medication and an effective accompanying hygiene management. To maintain effective parasite control, efficacy monitoring of the control measures should be implemented.